Комплексная многокритериальная оценка очагов ядерного поражения на основе анализа иерархий при создании системы радиационного мониторинга чрезвычайных ситуаций военного характера - Петрухин, Сергей Юрьевич; Писня, Леонид Андреевич; Чернявский, Игорь Юрьевич (Харківський національний університет Повітряних Сил ім. Івана Кожедуба, 2017)
В работе проводится комплексная оценка вклада «необходимых и достаточных» параметров ядерного взрыва для корректной оценки ситуации в очагах ядерного поражения на основе метода анализа иерархий Т. Саати. Практика комплексной многокритериальной оценки очагов ядерного поражения позволяет более глубоко исследовать взаимное воздействие поражающих факторов ядерного взрыва различной мощности, вида и типа ядерного боеприпаса, что, безусловно, показывает перспективы дальнейшего развития экспертно-аналитического оценивания в системах радиационного мониторинга чрезвычайных ситуаций военного характера.

In this paper, an attempt is made to evaluate the contribution of the so-called «necessary and sufficient» parameters of the BND by applying the method of hierarchical analysis (MHA) by T. Saati adapted for the problems under consideration in terms of the modified verbal interpretation of the values of the scale of pairwise comparisons. The essence of the application of the MHA is: first, in the decomposition of the stages of the tasks of estimating the BND in the form of a hierarchy consisting of subcriteria, criteria, factors and alternatives to the consequences with the displayed links between the individual elements; secondly, in the construction of matrices of paired comparisons of elements on the basis of expert judgments; thirdly, in calculating the priorities and importance of the elements, with further processing of expert judgments, the results of which determine the generalized weighted relative degree of interaction or interdependence of all elements of the hierarchy, which is expressed in a standardized numerical form in the form of global priorities. With this approach, the analytical approach of constructing a tree of events and consequences with expert procedures of pairwise comparisons of the importance of elements is combined, using algebraic matrix theory, and allows to consider the situation integrally «from top to bottom» and «from bottom to top», while including all available data about the elements, and to evaluate their weight contributions to the decision, that is, to find solutions in conditions of multicriterion. The results of the evaluation of the contribution of the initial «necessary and sufficient» parameters of a nuclear explosion (NE) of different power, TNE and TNA make it possible, under the uncertainty of the initial information, to correctly assess the emergent situations in BND in the framework of radiation monitoring of military emergencies. This fact points to the obvious need to take into account the spectrum of neutron radiation in forecastingthe boundaries of nuclear damage. As a sufficient additional information for making adequate and effective boundaries of nuclear damageforecasting, it is advisable to adopt the spectrum of the neutron radiation of the nuclear explosion. The analysis carried out by experts shows that when assessing boundaries of nuclear damage on both the basis of the type of nuclear explosion, the power of nuclear explosion, and the type of nuclear ammunition, the source of radiation mechanical damage (BND-2). It is important to note that in assessing this situation, the determination of the power and height of a nuclear explosion can be considered necessary parameters, and the determination of the spectral characteristics of the neutron radiation of nuclear radiation is sufficient.
Comprehensive multi-objective evaluation of foci of nuclear lesions on the basis of analysis of hierarchies when creating emergency radiation monitoring system of a military nature
Keywords: взрыв ядерный; метод анализа иерархий; поражение радиационно-механическое; поражение радиационно-термическое; эквивалент тротиловый; nuclear explosion; method of hierarchical analysis